A Cross-Sectional Analysis to Evaluate Knowledge, Attitude and Precautionary practices towards COVID-19 among mothers in a tertiary care hospital - Kamalakannan, Santosh Kumar (Halo 194 Scientific Journal of Emergency Medicine, 2022)
Abstract: Background: Knowledge, attitude and Precautionary practices towards COVID-19 among mothers plays an important role in reducing the spread of the infection and helps in the control of the pandemic. It also provides an insight about the role of media in controlling the pandemic. Objective: To assess knowledge, attitude and precautionary practices (KAP) towards COVID-19 among mothers in a tertiary care hospital. Methodology: This was a questionnaire-based cross-sectional analysis pertaining to COVID-19 which was conducted at a tertiary care obstetric facility in India among 100 consenting mothers. The consenting mothers were assessed for demographic details and KAP score (knowledge-8 questions, attitude-7 questions and precautionary practices-5 questions).